Visibility, Connectivity, Agency: Journalism's Prospects in an Age of Automated Social News Sharing. Issue 8 (14th September 2021) - Martin, Fiona R.
Abstract: The visibility of news on social media platforms is now as much mediated by opaque algorithmic power as quantifiable social news sharing. As public interest journalism has been transformed and even held to ransom by platformization, and its metrification of news value, there are ways for the news media to reassert their significance and independence, while building the post-scale engagement necessary to sustain its move from advertising to audience-based revenues. Regulatory activism, engagement re-orientation, and deeper research into commendary cultures offer avenues for journalism to reconfigure its relationship to platform power in an age of social news sharing.